ANALISIS KEKERASAN BAJA S45C DENGAN PROSES HEAT TREATMENT UNTUK PENGGUNAAN BAHAN PISAU CRUSHER PENCACAH PLASTIK - ariyanto ariyanto; Eko Yudo (Manutech : Jurnal Teknologi Manufaktur, 2022)
The Heat treatment process is carried out to change the mechanical properties of a steel. Changes that are expected to produce new better mechanical properties so that they can be applied to a mechanical system. One of the benefits that can be obtained is the increase in the value of the hardness needed. The hardening process carried out on S45C medium carbon steel material containing carbon by 0.45%. The heating process is carried out using an electric oven. The heating process is carried out using an electric oven. The heating process begins with heating the steel at several different temperature levels then followed by a quenching process with several different cooling media.  After the quenching process is carried out, the steel is tempered at a temperature of 500oC and measured hardness value using a hardness tester  , measurements on the HRA. From several parameters of heat treatment carried out obtained optimal values at a heating temperature of 8500C with brine cooling media. The value of the hardness of the material obtained is 68 HRA. In addition to an increase in the hardness value of steel, there is also a change in the microstructure, the changes in the microstructure that occur are the higher the hardness value of steel, the more the amount of perlite.